Meningkatkan Keterampilan Literasi Informasi dalam Pembelajaran Sejarah Menggunakan Metode Double Loop Problem Solving (DLPS) - Laili Hesti Yulianti; Murdiyah Winarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
Information literacy skills in history learning are important skills to be developed. This research is motivated by the low information literacy skills of students in learning history. These indications can be seen from the ability to analyze the connectedness of historical events and the ability to process student information. Based on these problems, the researchers formulated several problems that were taken in the study including: first, how to plan history learning using the Double Loop Problem Solving (DLPS) method through E-Learning. Second, how to apply history learning using the Double Loop Problem Solving (DLPS) method through E-Learning. Third, how to improve information literacy skills using the Double Loop Problem Solving (DLPS) method in learning history through E-Learning. [F1] Fourth, How to overcome obstacles in using the Double Loop Problem Solving (DLPS) method in history learning through E-Learning. This study aims to improve students' information literacy skills in learning history. This study uses the research design of Kemmis and McTaggart which includes planning, implementation, observation, and reflection. The researched aspects of information literacy skills are recognizing needed information, accessing relevant information, selecting and comparing information from different sources, evaluating appropriate information, organizing and using information efficiently, combining and constructing information into knowledge. new, and communicating and reflecting information. Based on the results of research conducted, the use of Double Loop Problem Solving (DLPS) can improve students' information literacy skills in learning history. In the first cycle the average percentage is 50.4%, the second cycle is 60%, and the third cycle is 82.8%.